A formação ética do estudante no ensino médio: realidade e perspectivas na educação nacional - Silva, Patrícia Aparecida da (2023)
The research has as its object of study, the ethical formation of high school students mediated by the learning of philosophy, in the context of national education. Of a theoretical nature, it is developed using specialized literature, taking into account the results of research already carried out on the subject and advanced reflections by scholars who have dedicated themselves to the subject. It assumes as a theoretical reference the understanding of the role of philosophy in ethical formation in the educational process based on the positions of Aristotle and Immanuel Kant, referring to the role of Philosophy in the emancipation of the subject, in its human formation and in the exercise of critical reflection as well as the idea of supreme good that is primordial for the harmonious life in society. In addition to resuming Aristotelian and Kantian texts for this foundation, the investigation resorted to a review of the literature related to the ethical formation of young people. become relevant and necessary for the ethical and political formation of young people in high school.